Self-Concept Development through Fashion Products: A Case Study among Sneakerheads in Indonesia - Albert Albert (Journal Research of Social Science, Economics, and Management, 2025)
This study examines how wearing Nike Air Jordan sneakers contributes to self-concept formation among sneakerheads in the Indonesia Sneaker Team (IST) community. Using Symbolic Interaction Theory and self-concept framework, this qualitative research explores the relationship between fashion products and identity construction. The study employed structured interviews with seven key informants, including IST leaders, active members, collectors, and content creators, selected through purposive sampling with specific criteria. Data were analyzed using thematic analysis following Daymon and Holloway's framework. Results indicate that Nike Air Jordan functions as a symbol representing identity, nostalgia, and personal values. The Mind element reveals that Air Jordan carries meanings of basketball passion, Michael Jordan idolization, and streetwear culture. The Self element shows enhanced confidence, coolness, and unique style expression. The Society element demonstrates how sneakerheads navigate between personal identity and social expectations. Self-concept formation occurs through three components: self-image (enhanced appearance and confidence), self-esteem (positive reactions from others), and ideal-self (inspiration from Michael Jordan's values). The study reveals that sneakerheads view Air Jordan as more than fashion items—they represent personal identity, motivation, and networking opportunities. These findings contribute to understanding consumer behavior in fashion products and provide insights for marketing strategies targeting sneaker enthusiasts.